An improved methodology for reactive power management in grid integrated solar PV system with maximum power point condition. (15th March 2020) - Mishra, Manash Kumar; Lal, Vivek Nandan
Highlights: A modified mathematical methodology is proposed to derive P-Q capability curves of grid-integrated PV system. Achieve all the possible set of working points (P-Q limit) within the stable region of operation. Managing the reactive power injection into the grid at MPP condition for various environmental conditions. Verify the effectiveness of the proposed mathematical methodology using OPAL-RT. Abstract: The grid-integrated solar photovoltaic (PV) inverter is generally used to provide active power (P) support to the distribution grid operated at maximum power point (MPP) condition. Moreover, it should also be capable of providing reactive power support (Q) to the distribution grid. Therefore, an appropriate range of reactive power should be known at MPP condition to ensure satisfactory operation of the grid-integrated PV system (GIPV). In this work, an improved mathematical methodology is proposed to derive the P-Q capability curve of GIPV for managing the reactive power injection into the grid at MPP condition for various environmental conditions. By evaluating all the possible set of working point within the stable region of operation, this methodology is used to obtain reactive power limits of a utility-scale single-stage three-phase PV system connected to the IEEE 33 bus distribution grid. The considered PV system is simulated using software-in-the-loop (SIL) environment based on OPAL-RT OP4510 real-time digital simulator with coordinated closed-loop control of dc-link voltage controller, maximum power point tracking (MPPT) controller, and active and reactive power controller. To validate the effectiveness of the improved mathematical methodology, the reactive power injection to the grid is changed, and the corresponding active power injection to the grid are measured, which are compared with the P - Q values obtained from the improved mathematical methodology.